Repercussões do Programa de Avaliação da Alfabetização (PROALFA) na ação docente: a perspectiva de professores de uma escola estadual em Viçosa-MG - Vieira, Raquel Arrieiro (Universidade Federal de São Carlos, 2022)
This work analyzed the perceptions about the external evaluation of the Literacy Assessment Program (Proalfa) of teachers who teach for the 3rd year of elementary school at a state school in the city of Viçosa/MG. We tried to understand the following aspects of this policy in the context of practice: its legal contributions, the Simave evaluation instruments, and its consolidation in the state of Minas Gerais; how do teachers have access and how test data are communicated/processed at school; the way in which teachers use the results of external assessments; whether Proalfa results are used in school planning; the meanings attributed to Proalfa, given the demands established by the State Department of Education (SRE). To fulfill the objectives of this qualitative work, instruments such as semi-structured interviews and a conversation wheel were used. The articulation between the theoretical and bibliographic reference and the reports shared by the teachers led to the creation of four axes of analysis: perceptions attributed by the teachers to Proalfa; Proalfa results: uses and forms of appropriation at school; teaching improvement instruments: the case of the PIP and Systemic Assessments of Learning, and collaborative work within the scope of Proalfa. The research results indicate that Proalfa, as an educational public policy created in the neoliberal logic, affects different aspects of the school context: in the reconfiguration of school practices, with the training of students for external assessments, aiming at good numerical results; in the curricular narrowing, caused by the misunderstanding between the reference matrix and the curricular matrix; in continuing education, realizing that the discussions about the difficulties in the use and critical appropriation of the evaluation results are shallow and not very reflective; in the teaching improvement instruments, whose focus is to meet the policy needs and not the students' learning difficulties; in the increase of teaching work, causing an overload in their attributions to meet the demands of the SRE.
Repercussions of the literacy evaluation program (PROALFA) on teaching action: a teacher's perspective state school in Viçosa-MG
Keywords: Proalfa; Formação de professores; Avaliação externa; Contexto da prática; Teacher training; External evaluation; Practice context; CIENCIAS HUMANAS::EDUCACAO